A live attenuated Salmonella Typhimurium vaccine dose and diluent have minimal effects on the caecal microbiota of layer chickens - Khan, Samiullah; McWhorter, Andrea R.; Andrews, Daniel M.; Underwood, Gregory J.; Moore, Robert J.; Van, Thi Thu Hao; Gast, Richard K.; Chousalkar, Kapil K. (Frontiers in Veterinary Science, 2024)
Among the Salmonella reduction strategies in poultry production, one option is to use a Salmonella vaccine. The aim of vaccinating layer flocks is to reduce the shedding of wild-type Salmonella in the poultry environment, thereby reducing the contamination of poultry products (eggs and meat). Nutritive diluent and higher dose of vaccine may enhance its colonisation potential in the gut of chickens. In this study, a commercially available live attenuated vaccine (Vaxsafe® ST) was reconstituted in different media and delivered orally to day-old chicks at three different doses (10 7 , 10 8 and 10 9 CFU/chick). Gut colonisation of the vaccine strain and the effects of vaccination on gut microbiota were assessed in commercial layer chickens. The vaccine diluent and dosage minimally affected microbiota alpha diversity. Microbiota beta diversity was significantly different (P < 0.05) based on the vaccine diluent and dose, which indicated that the vaccinated and unvaccinated chickens had different gut microbial communities. Differences were noted in the abundance of several genera including Blautia, Colidextribacter, Dickeya, Enterococcus, Lactobacillus, Pediococcus and Sellimonas. The abundance of Colidextribacter was significantly lower in chickens that received vaccine reconstituted in Marek's and water diluents, while Lactobacillus abundance was significantly lower in the water group. The highest vaccine dose (10 9 CFU/chick) did not significantly alter (P > 0.05) the abundance of microbial genera. Chicken age affected the microbiota composition more significantly than vaccine dose and diluent. The abundance of Lactobacillus, Blautia, Caproiciproducens, Pediococcus and Colidextribacter were significantly higher on day 14 compared with day 7 post-vaccination. The Salmonella Typhimurium vaccine load in the caeca was not significantly affected by diluent and vaccine dose; however, it was significantly lower (P < 0.0001) on day 14 compared with day 7 post-vaccination. Overall, S. Typhimurium vaccine minimally affected the gut microbiota and structure of layer chicks, whereas changes in microbiota were more significant with chicken age.